Assessing hydrofacies and hydraulic properties of basaltic aquifers derived from geophysical logging - Navarro, Juan [UNESP]; Teramoto, Elias Hideo [UNESP]; Engelbrecht, Bruno Zanon [UNESP]; Kiang, Chang Hung [UNESP] (Soc Brasileira Geologia, 2020)
Basaltic aquifers are an important source of water supply in many regions worldwide. Because of their cooling process, flood basalts normally have complex internal structures and unpredictable permeable zone distribution. Geophysical profiling is a reliable tool used to identify the vertical variations of physical properties within the flood basalts, mainly to distinguish between low and high permeability intervals. In this study, a detailed analysis of drill cuttings, and geophysical logging of two depth wells helped to identify the typical response of main facies of flood basalts in the Serra Geral aquifer system. The evidence obtained from this work confirms that flood basalts may be classified as multilayer aquifer systems in which a highly permeable top covers a center with low permeability as a result of recurrent floods. In several cases, permeable layers are represented by a weathering horizon developed between two flood events. This study uses an empirical model to estimate the porosity based on acoustic velocity logging. A useful model based on a well-established Kozeny-Carman model was developed to predict the permeability of basaltic rocks using porosity data. The results obtained allow to identify the permeable intervals of basaltic aquifers and to estimate their hydraulic properties.
Keywords: flood basalts; geophysical logging; basaltic aquifers; Serra Geral Aquifer